Encyclopedia of Industrial Biotechnology 2010
DOI: 10.1002/9780470054581.eib290
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes, Enolate Reductases “Old Yellow Enzyme”

Abstract: Reported enoate reductase activity is mostly displayed by enzymes belonging to the “Old Yellow Enzyme” family of flavoproteins. They have received increased interest over the last couple of years due to their huge potential in biocatalysis. These FMN‐containing enzymes catalyze the asymmetric reduction of activated C═C bonds at the expense of a nicotinamide cofactor, producing up to two chiral centers. They are also involved in other reductive processes, such as cleavage of nitrate esters, reduction of aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the majority of enoate reductases accept both NADH and NADPH at similar rates (Hall et al, 2010). In order to examine the potential of the 2-propanol/ADH-A system for the recycling of NADH, YqjM from Bacillus subtilis (Kitzing et al, 2005) and NCR from Zymomonas mobilis (Müller et al, 2007) were applied for the bioreduction of various substrates.…”
Section: Lilialmentioning
confidence: 99%
“…Previous studies have shown that the majority of enoate reductases accept both NADH and NADPH at similar rates (Hall et al, 2010). In order to examine the potential of the 2-propanol/ADH-A system for the recycling of NADH, YqjM from Bacillus subtilis (Kitzing et al, 2005) and NCR from Zymomonas mobilis (Müller et al, 2007) were applied for the bioreduction of various substrates.…”
Section: Lilialmentioning
confidence: 99%
“…Biotransformation of suitable precursors is an attractive, sustainable and cost-effective alternative to “chemical” reduction: the biocatalytic analog relies on ERs to perform the reduction of activated C=C bonds. ERs are Flavine MonoNucleotide (FMN)-dependent enzymes belonging to the so-called “old yellow enzyme” (OYE) family, and have been intensely investigated over the past years in view of their applicability in preparative-scale biotransformations [80,81,82].…”
Section: Biocatalytic Production Of Flavors and Fragrances By Ncysmentioning
confidence: 99%
“…The diversity of activating groups accepted by OYEs has led to the development of a remarkable range of chiral compounds that could potentially be used as building blocks in the synthesis of larger molecules. Comprehensive reviews have been published recently. , …”
Section: Techniques Biocatalystsmentioning
confidence: 99%